STUDI AKURASI ALAT TERMOMETER NON-CONTACT DENGAN MENGGUNAKAN INFRA RED PADA TERMOMETER DIGITAL - Salomo Sijabat; Dyna Grace Romatua Aruan; Dedy Antoni; Barmencius Simarmata (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2021)
A thermometer is a tool used to measure body temperature. To make it easier to measure body temperature, a non-contact thermometer using infrared and a digital thermometer is used to get faster results compared to a manual thermometer. Non-contact thermometers using infrared measure body temperature by placing them at the point, axillary, and rectal, while infrared thermometers are used to measure the temperature emitted by the tympanic membrane. digital thermometer. The results of the accuracy test obtained are the total null value of the first test result obtained at 1.34°С compared to the digital thermometer tool. digital. The distance needed by this tool to read the human body temperature is +/- 3cm. The time needed to measure temperature with a digital thermometer is 10-15 seconds. From the results of the most accurate distance measurement for infrared thermometer measurements, it is 2 cm.